Membaca Ulang Injil Dan Kebudayaan Dalam Tradisi Batak Toba: Re-reading the Gospel and Culture in the Batak Toba Tradition - Irvan Hutasoit (Journal of Religious and Socio-Cultural, 2023)
How can theology rationalize an irrational object, namely: God? If the effort to study theology wants to rationalize these irrational objects, then theology cannot be separated from scientific branches outside of itself. This article aims to re-read the Bible and Culture in the Toba Batak tradition. The research method used is the cultural sociology approach. While the result of this research is that the church is confronted with the postmodern perception of the human mind. In it there is an awareness that on earth there are many truths that are scattered. Each truth does not conflict with each other, but complements one another, because the existence of one truth is only real when it is side by side with other truths. This belief must of course be expressed in the utterances of words and sentences in the church rites room, both verbally and in writing. Bagaimana teologi bisa merasionalkan suatu objek yang tidak rasional, yaitu: Allah? Apabila usaha pembelajaran teologi hendak merasionalkan objek yang tidak rasional tersebut, maka teologi tidak bisa lepas dari cabang keilmuan di luar dirinya. Artikel ini bertujuan membaca ulang Injil dan Kebudayaan dalam tradisi Batak Toba. Metode penelitian yang digunakan dengan pendekatan sosiologi budaya. Sednag hasil penelitian ini adalah gereja diperhadapkan pada persepsi pikiran manusia yang Postmodern. Di dalamnya ada kesadaran bahwa di muka bumi banyak kebenaran yang bertebaran. Masing-masing kebenaran tidak saling bertentangan, tetapi mengisi antara yang satu dengan lainnya, sebab eksistensi kebenaran yang satu baru nyata apabila bersanding dengan kebenaran yang lainnya. Keyakinan ini tentu harus dituangkan dalam tuturan-tuturan kata serta kalimat dalam ruang ritus gereja, baik secara verbal maupun tertulis.